Thiol‐Disulfide Exchange as a Route for Endosomal Escape of Polymeric Nanoparticles. (8th August 2022) - Kanjilal, Pintu; Dutta, Kingshuk; Thayumanavan, S
Abstract: Endosomal entrapment has remained the major bottleneck for cytosolic delivery of nanoparticle‐based delivery systems. Uncovering fundamentally new pathways for endosomal escape is therefore highly sought. Herein, we report that disulfide bonds can enhance endosomal escape through contacts with cellular exofacial thiols, in addition to facilitating cellular uptake. Our results are supported through comparative analysis of polymeric nanogels with variable accessibility to disulfide bonds by placing these functionalities at the core or the shell of the nanogels. The findings here inform future chemical design of delivery vehicles. Abstract : Polymeric nanogels with judiciously placed disulfide bonds have been synthesized and tested for cellular uptake and endosomal escape. Comparison with their non‐disulfide counterparts shows that disulfide moieties play a key role in endosomal escape.